MANAGEMENT SYSTEM IN CIVIL SERVANT CAREERS - Maulana Muzaky; Syahran; Mukhaer Pakkanna (Jurnal Perilaku dan Strategi Bisnis, 2023)
The formation of Civil Servant Career Path cannot be separated from intervention of political officials who take part in government bodies, the principle of neutrality of Civil Servants is at stake. Analysis of the Influence of the Merit System, Talent Scouting, and Talent Pool on Career Path of Civil Servants is the main objective of this research. To achieve the research objectives, the research object and population are all Civil Servants of the Government of Magelang Regency, Central Java, Indonesia, totaling 6627 civil servants. Sample determination is based on the provisions of Slovin Formula margin of error of 0.05 = 378 civil servants, using Random Sampling method. The data analysis technique uses Structural Equation Modeling (SEM). The research results show that Merit System has positive and significant effect on Career Path. Talent Scouting has positive and significant effect on career path. And Talent Pool has positive and significant effect on Career Path.